Conceptual search of songs using domain ontology and semantic links. (2017) - Lachtar, Nadia; Bahi, Halima; Bouras, Zine Eddine
Songs retrieval process is complex and implies multiple facets. Nowadays, the most common way of searching songs is through a combination of factual and cultural metadata or by lyrics. Owing to the poor indexing techniques, these systems cannot completely satisfy the users' requests. In this paper, we suggest the use of domain ontology and semantic links to index a collection of songs and perform a conceptual search that offers a benefit way to complement metadata-based methods. A set of experiments were carried over a dedicated dataset and show the superiority of our approach when compared with classical one.